Specialization, Comparative Advantage, and the Sexual Division of Labor - Siminski, Peter; Yetsenga, Rhiannon (Journal of Labor Economics, 2022)
Recent work situates gender norms as a key driver of the sexual division of labor. But the explanatory power of Becker’s comparative advantage explanation is still not well understood. Drawing on unique data, we test the predictions of a formal Beckerian model. We complement this by proposing and analyzing new measures of specialization. We show that comparative advantage plays little or no role in the sexual division of labor within couple households. Absolute advantage also plays no role in specialization for same-sex couples, and this is not explained by having fewer children.